Robotics: Science and Systems XIII 2017
DOI: 10.15607/rss.2017.xiii.026
|View full text |Cite
|
Sign up to set email alerts
|

Time-Lapse Light Field Photography for Perceiving Non-Lambertian Scenes

Abstract: Abstract-Robust robotic perception and manipulation of household objects requires the ability to detect, localize and manipulate a wide variety of objects, which may be mirror reflective like polished metal, glossy like smooth plastic, or transparent like glass; for example, picking a metal fork out of a sink full of running water or screwing a metal nut onto a bolt. Existing perceptual approaches based on photographs only take into account the average intensity of light arriving at each pixel from one directi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Saccades, foveation and related ideas have been studied in robotics and active vision for many years [1,3,18,44,12,19,7]. In addition, foveal designs to enable high-quality imaging are also common [45,27,43,13].…”
Section: Related Workmentioning
confidence: 99%
“…Saccades, foveation and related ideas have been studied in robotics and active vision for many years [1,3,18,44,12,19,7]. In addition, foveal designs to enable high-quality imaging are also common [45,27,43,13].…”
Section: Related Workmentioning
confidence: 99%
“…The use of light field perception in robotics is still relatively new. Oberlin and Tellex [19] proposed a time-lapse light field capturing pipeline for static scenes by mounting a RGB camera on the end-effector of the robot and moving in a designed trajectory. Tsai et al [28] introduced a algorithm for distinguishing refracted and Lambertian features from light field image.…”
Section: B Light Field Photographymentioning
confidence: 99%
“…(1) Each surface point emits light rays ρ in each channel as a Gaussian over (r, g, b) with mean (µ r , µ g , µ b ) and variance (σ 2 r , σ 2 g , σ 2 b ) which means ρ = N (λ; µ c , σ 2 c ), c ∈ {r, g, b}, as similarly assumed by Oberlin and Tellex [21]. Under constant lighting condition we assume every point in the scene shares the same variance for the same color channel which means σ c = σ c , c ∈ {r, g, b} for all points in the scene.…”
Section: A Formulationmentioning
confidence: 99%
“…Light field photography offers considerable potential for robot perception in scenes with translucency. For example, Z Oberlin and Tellex [21] found that a high-resolution camera on the wrist of a robot manipulator can capture light fields for a static scene. By moving the robot end-effector in a designed trajectory, this time lapse approach to light field capture was demonstrated as capable of manipulating transparent and reflective objects.…”
Section: Introductionmentioning
confidence: 99%